Periconceptional use of cod liver oil, a vitamin D source, could decrease the risk of CHD in offspring. (28th October 2020) - Zhao, Anda; Zhao, Kena; Xia, Yuanqing; Yin, Yong; Zhu, Jianzhen; Hong, Haifa; Li, Shenghui
Abstract: Objective: To explore if there is association between vitamin D supplementation through cod liver oil ingestion around the periconceptional period and the risk of developing severe CHD in offspring. Furthermore, we would examine the interaction between vitamin D and folic acid supplementation in the association. Methods: A case–control study was conducted in Shanghai Children's Medical Center, in which, a total of 262 severe CHD cases versus 262 controls were recruited through June 2016 to December 2017. All children were younger than 2 years. To reduce potential selection bias and to minimise confounding effects, propensity score matching was applied. Results: After propensity score matching, vitamin D supplementation seemed to be associated with decreased odds ratio of severe CHD (odds ratio = 0.666; 95% confidence intervals: 0.449–0.990) in the multivariable conditional logistic analysis. Furthermore, we found an additive interaction between vitamin D and folic acid supplementation (relative excess risk due to interaction = 0.810, 95% confidence intervals: 0.386–1.235) in the association. Conclusion: The results suggested that maternal vitamin D supplementation could decrease the risk of offspring severe CHD; moreover, it could strengthen the protective effect of folic acid. The significance of this study lies in providing epidemiological evidence that vitamin D supplementation around the periconceptional period could be a potential nutritional intervention strategy to meet the challenge of increasing CHD.